The Elemental Sulfur-Responsive Protein (SipA) from the Hyperthermophilic Archaeon Pyrococcus furiosus Is Regulated by Sulfide in an Iron-Dependent Manner - Clarkson, Sonya M. (American Society for Microbiology (ASM), 2010)
The gene (sipA) encoding the sulfur-induced protein A (PF2025) is highly upregulated during growth of Pyrococcus furiosus on elemental sulfur (S(0)). Expression of sipA is regulated by sulfide, the product of S(0) reduction, but in an iron-dependent manner. SipA is proposed to play a role in intracellular iron sulfide detoxification.